2010
DOI: 10.1002/chem.201000044
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design of High‐Spin Polycyclic Hydrocarbons

Abstract: High-spin organic structures can be obtained from fused polycyclic hydrocarbons, by converting selected peripheral HC(sp(2)) sites into H(2)C(sp(3)) ones, guided by Ovchinnikov's rule. Theoretical investigation is performed on a few examples of such systems, involving three to twelve fused rings, and maintaining threefold symmetry. Unrestricted DFT (UDFT) calculations, including geometry optimizations, confirm the high-spin multiplicity of the ground state. Spin-density distributions and low-energy spectra are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…[6] The possibility of cutting graphene sheets to create magnetic nanoflakes to substitute, saturate, or subtract carbon atoms in the graphene itself is now a hot topic. [7] The authors have proposed some logical recipes to create high-spin fused polycyclic aromatic systems, [8] and to assemble them into ferromagnetic or antiferromagnetic architectures, which may be discrete or periodic. [9] A guiding tool to predict the spin multiplicity of any alternant hydrocarbon (i.e., free from odd-membered rings) is the so-called Ovchinnikov's rule, proposed in 1978, [10] later established more rigorously by Lieb, and known in solid-state physics as Lieb's theorem.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The possibility of cutting graphene sheets to create magnetic nanoflakes to substitute, saturate, or subtract carbon atoms in the graphene itself is now a hot topic. [7] The authors have proposed some logical recipes to create high-spin fused polycyclic aromatic systems, [8] and to assemble them into ferromagnetic or antiferromagnetic architectures, which may be discrete or periodic. [9] A guiding tool to predict the spin multiplicity of any alternant hydrocarbon (i.e., free from odd-membered rings) is the so-called Ovchinnikov's rule, proposed in 1978, [10] later established more rigorously by Lieb, and known in solid-state physics as Lieb's theorem.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our very recent studies on high-spin polyaromatic hydrocarbon molecules showed satisfactory agreements between EVB calculations and high level ab initio methods, such as differencededicated configuration interaction and complete active space with second order perturbation theory. 25 Recently, we employed it to study the open-shell singlet ground state of polyacene, 26 by solving the model Hamiltonian with the density matrix renormalization group method (DMRG), [27][28][29] and the results agreed with DMRG on the complete-active-spaceself-consistent-field (CASSCF) or the active-space variational two-electron reduced-density-matrix-CASSCF. 11,13,26,30,31 …”
Section: Introductionmentioning
confidence: 99%
“…Values of and have also been calculated in non-doped nickelates = 0.6 and = 30 . Much smaller values of = 0.3 are observed in organic magnetic systems [22] as the magnetic orbitals are delocalized over several carbon centers.…”
Section: Computational Informationmentioning
confidence: 99%